Size of Subcortical Band Heterotopia Influences the Susceptibility to Hyperthermia-Induced Seizures in a Rat Model - Moustaki, Kalliopi; Buhler, Emmanuelle; Martinez, Robert; Watrin, Françoise; Represa, Alfonso; Manent, Jean-Bernard (Frontiers in Cellular Neuroscience, 2019)
Studies conducted in human and rodent models have suggested that preexisting neurodevelopmental defects could predispose immature brains to febrile seizures (FS). However, the impact of the anatomical extent of preexisting cortical malformations on FS susceptibility was never assessed. Here, we induced hyperthermic seizures (HS) in rats with bilateral subcortical band heterotopia (SBH) and found variable degrees of HS susceptibility depending on inter-individual anatomical differences in size and extent of SBH. This indicates that an association exists between the overall extent or location of a cortical malformation, and the predisposition to FS. This also suggests that various predisposing factors and underlying causes may contribute to the etiology of complex febrile seizures.